Christmas Light Flasher / Azizah Mohd Puat and Rosnani Abdul Aziz - Mohd Puat, Azizah; Abdul Aziz, Rosnani (2003)
Widely regarded as the consummate digital diagnostic tool, our probe Christmas Light Flasher are device that is prudent to keep on the work bench. Now while many others commercial modal are available to market and prohibitive in cost, we find there is still a way to have our own Christmas Light Flasher by build it ourselves. This Christmas Light Flasher is very useful as a home accessory. Actually when festivals season, like Hari Raya, Deepavali, Christmas, Chinese New year and others. Its also very interested us to know how the step of light running with are pattern. The light should operate in the same sequence as thee LED’s. Furthermore, the hardware development of or project also earned less cost because it only uses less of components. The control in the Christmas Light Flasher is supply of transformer 6V-0-6V (100mA) to generate all the main components. The front panel LED’s should flash in the sequence described earlier. Added a speed control pot, this should vary the seed as expected. Disconnect thee unit from the main and connect a set of Christmas lights to each output.